La higiene escolar en la ciudad de México en los inicios del siglo XX - Chaoul, María Eugenia (El Colegio de México, A.C., 2012)
This text explores how the incorporation of doctors into Porfirian schooling project gave place to an institutional change and to the use of Mexico City schools not only as educational centers, but also as social agencies for colving urban problems. During the first years of the twentieth century, the Scretaría de Instrucción Pública y Bellas Artes (Ministry for Public Instruction and Beaux Arts), opening as a specialized manager, aimed at regulating school hygiene permanently as a matter of public policiy. The scientific backing of doctors allowed the expansion of public intervention and gave place to changes in the estabished rules, increasing government responsabilities and creating new forms of collective action. School hygiene as public policy became manifest in how hygienists reorganized, rationalized, and cleansed educational facilities, linking schools to he surrounding city and creating crossing points between schools and families.